Perpetuating the Academic Gender Gap - Baker, Maureen (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
Women university faculty have increased since the 1970s but the gender gap continues. This paper, based on interviews with New Zealand academics and international research, suggests that family relationships interact with institutional priorities to slow women's progression through the ranks. The strengthening emphasis on peer-reviewed and funded research seems daunting to some academics, especially mothers with young children.